Maxi's secrets : (or what you can learn from a dog) - Plourde, Lynn (Nancy Paulsen Books, 2016)
"Fifth-grader Timminy, who's small for his age and new in town, isn't eager to start middle school--but he gets a great consolation prize in Maxi, a big, deaf, lovable dog"--